The Past Is Not Yet Over: Remembrance, Justice and Security Community in the Western Balkans - Subotić, Jelena (Journal of Regional Security, 2018)
Twenty years since the onset of the wars of Yugoslav secession, the countries of the Western Balkans continue to nurture narratives of the past that are mutually exclusive, contradictory, and irreconcilable. In this essay, I argue that there is a direct link between ways in which different states remember their pasts and obstacles to the building of long-term regional security community in the region. I propose that remembrance of the past and historical justice for past wrongs shape choices policymakers make, by making some options seem unimaginable, while others inevitable. The power that narratives of past violence and injustice hold on policymakers is particularly significant as the region advances toward European integration. The efforts to “clean up” the past – through education reform and memorialization projects – should not be thought of as secondary initiatives, but as critically needed steps in pursuit of regional stability based on sustainable security community.